Two-way street : how smartphones and the social web impact the traveller’s liminal gaze - Duffy, Andrew (2019)
Travellers have long inhabited a liminal position between home and away. Now they also have a bridging foot in cyberspace, as Internet-enabled smartphones mediate their travel experience. Social-web-assisted mobility means that gazing down at a smartphone screen can either enhance or hamper a traveller’s movement through a destination and their interaction with place and its inhabitants, either distancing them from local people or offering new means to connect with hosts and enhance the travel experience. An Internet-linked smartphone is like a portal through which the traveller can gaze into different directions. Further, it is not just a question of which direction they choose; the choice will impact on the gazer and the performance of the gaze, potentially compromising attempts to view a place through independent eyes as the traveller’s imaginings of the foreign sphere are influenced by the social web. This paper reviews the literature on how travellers use the Internet before, during, and after a trip, and suggests the concept of the liminal gaze—in which an individual chooses between different directions to look at and different spheres to focus on—as a tool to examine smartphone-mediated interaction between people, and between people and place.